2017
DOI: 10.4187/respcare.05298
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Aerosol Therapy

Abstract: Inhaled medications are the mainstay of therapy for many pediatric pulmonary diseases. Device and delivery technique selection is key to improving lung deposition of inhaled drugs. This paper will review the subject in relationship to several pediatric clinical situations: acute pediatric asthma, transnasal aerosol delivery, delivery through tracheostomies, and delivery during noninvasive and invasive mechanical ventilation. This review will focus on the pediatric age group and will not include neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…The current approach did not differentiate between aerosol that was released prior to inhalation, or aerosol that was possibly exhaled after inhalation. While the use of collection filters has been widely used as a suitable method to determine the inhalation dose [33,34], it might not be truly representative of a simulation of real exhalation. However, since the overall percentage of the inhaled dose is relatively small, it is assumed that the majority of the fugitive emissions consists of aerosol escaping prior to inhalation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current approach did not differentiate between aerosol that was released prior to inhalation, or aerosol that was possibly exhaled after inhalation. While the use of collection filters has been widely used as a suitable method to determine the inhalation dose [33,34], it might not be truly representative of a simulation of real exhalation. However, since the overall percentage of the inhaled dose is relatively small, it is assumed that the majority of the fugitive emissions consists of aerosol escaping prior to inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…Berlinski [34] reported that the aerosol size fraction exiting the tip of the tracheostomy tube was 1.20 to 1.77 µm. Berlinski [33] reported that aerosol changed its characteristics when travelling through a tracheostomy tube; the effects were more noticeable for nebulised aerosol than metered dose inhalers or valved aerosol reservoirs. Additionally, during simulated adult breathing with gas-flow rates of 10, 40 and 60 L/min, there were comparable trends between the nasal cannula and the tracheostomy interface.…”
Section: Discussionmentioning
confidence: 99%
“…This as noted often, but not always, involves stopping the putative causative drug(s). There are circumstances—such as, for example, therapy of HIV infection with antiretroviral drugs or asthma with albuterol (salbutamol)—during which therapy is continued in the presence of side effects with the expectation that these side effects will diminish or become more tolerable over time …”
Section: The Clinical Approach To Adverse Drug Reactionsmentioning
confidence: 99%
“…There are circumstances-such as, for example, therapy of HIV infection with antiretroviral drugs or asthma with albuterol (salbutamol)-during which therapy is continued in the presence of side effects with the expectation that these side effects will diminish or become more tolerable over time. [61][62][63][64] Management of the ADR in the context of an acute life-threatening event such as anaphylaxis involves a rapid and coordinated response addressing key issues such as airway, breathing, and circulation. 65 In the case of less acute presentations, the primary management strategy is to provide symptomatic relief in the anticipation that the symptoms will diminish and resolve over time.…”
Section: The Clinical Approach To Adverse Drug Reactionsmentioning
confidence: 99%
“…Another area of controversy was the use of Aerosol therapy via HHFNC. The delivery of nebulized medicines is generally affected by flow, type of system used, cannula size, and type of nebulizer used [28]. Respondents didn't specify if certain nebulizing devices were used on their wards while connected to HHFNC.…”
Section: Discussionmentioning
confidence: 99%